2017
DOI: 10.1111/1756-185x.12988
|View full text |Cite
|
Sign up to set email alerts
|

Association between leukocyte telomere length and angiogenic cytokines in knee osteoarthritis

Abstract: Aim: The aims of this study were to compare leukocyte relative telomere length (RTL) in knee osteoarthritis (OA) patients and healthy controls and to investigate associations between plasma angiogenic cytokine concentrations and leukocyte RTL.Method: Eighty knee OA patients and 60 age-matched controls were enrolled. Leukocyte RTL was assessed using real-time quantitative polymerase chain reaction (qPCR). Angiogenic cytokines were measured by a multiplex immunoassay.Results: Leukocyte RTL in knee OA patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…Notably, plasma hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF) and granulocyte-colony stimulating factor (G-CSF) levels were found to be negatively associated with leukocyte RTL. Therefore, that study indicated that high circulating angiogenic cytokine levels in the knees of patients with OA may reflect high oxidative stress and chronic inflammation, leading to subsequent telomere shortening (58). Indeed, overall oxidative stress can expedite telomere shortening either indirectly through increase in cell division, or directly acting on DNA telomere repeats, suggesting that redox balance is a prominent factor that regulates chondrocytes lifespan (59).…”
Section: Association Between Telomere Length Op and Oamentioning
confidence: 99%
“…Notably, plasma hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF) and granulocyte-colony stimulating factor (G-CSF) levels were found to be negatively associated with leukocyte RTL. Therefore, that study indicated that high circulating angiogenic cytokine levels in the knees of patients with OA may reflect high oxidative stress and chronic inflammation, leading to subsequent telomere shortening (58). Indeed, overall oxidative stress can expedite telomere shortening either indirectly through increase in cell division, or directly acting on DNA telomere repeats, suggesting that redox balance is a prominent factor that regulates chondrocytes lifespan (59).…”
Section: Association Between Telomere Length Op and Oamentioning
confidence: 99%
“…VEGF positively regulates telomerase activity in both in vivo and in vitro models (87,88). However, some epidemiological studies have shown that plasma VEGF is negatively or not correlated with TL (76,89). In addition, hepatocyte growth factor and granulocyte colony-stimulating factor, which contribute significantly both in physiological and pathological angiogenesis, were also found to be negatively correlated with TL in knee osteoarthritis patients (Table 1) (89).…”
Section: Biomarkers Related To Tlmentioning
confidence: 99%
“…However, most of the studies linking TL to inflammatory biomarkers were based on crosssectional design, and therefore, cannot explain the bi-directionality that exists between TL shortening and inflammation. It is, therefore, highly desirable to use data from longitudinal studies with large sample sizes in order to determine the evolution of various biomarkers at multiple time points, which will allow to better explore the telomere dynamics in relation with various chronic diseases (76,89,102,103).…”
Section: Biomarkers Related To Tlmentioning
confidence: 99%
“…In the context of OA, shorter telomere length was found in knee osteoarthritis patients with high levels of stress and pain [20], with a later study by the same authors largely confirming these results by observing shorter telomeres among individuals with the greatest burden of chronic knee pain [21]. Interestingly, a recent investigation demonstrated an association between angiogenic cytokines (i.e., hepatic growth factor, vascular endothelial growth factor, granulocyte-colony stimulating factor) and telomere length in knee OA, suggesting a potential role for these factors in cellular aging and OA pathogenesis [22]. …”
Section: Mechanisms Underlying Osteoarthritis Painmentioning
confidence: 75%